Determinants of Blood Pressure among Youth in Ajman, UAE (Nepal Journal of Epidemiology, 2010)
BackgroundYouth is a vulnerable group for developing almost all life-style related diseases. The present cross-sectional study was conducted to assess the determinants of blood pressure among entry year students in a medical university in Ajman, United Arab Emirates.Materials and Methods  One hundred and ten students from Gulf Medical University, Ajman, UAE participated in the study. A pretested structured questionnaire was used for data collection. Predictive Analytic Software 17 was used for data analysis. Chi-square test, Univariate and multivariate logistic regression were used.ResultsVariables such as tobacco use, duration of sleep, Body Mass Index and gender were considered to assess the association with blood pressure. The mean age of the students was 19 years with a SD of 1.9 years. The mean systolic and diastolic blood pressure was 113.5 (SD 12.0) and 73.7 (SD 11.2) respectively with mean BMI of 24.9 (SD 5.7). A statistically significant association was observed between gender and blood pressure (p